2021
DOI: 10.1155/2021/5539304
|View full text |Cite
|
Sign up to set email alerts
|

Serum ICAM-1 as a Predictor of Prognosis in Patients with Acute Ischemic Stroke

Abstract: Objective. Inflammation is one of the key mechanisms involved in functional impairment after stroke. Intercellular adhesion molecule-1 (ICAM-1) is an important inflammatory molecule in the body. The purpose of our study was to determine the correlation between ICAM-1 and the prognosis of acute ischemic stroke (AIS). Methods. 286 AIS patients treated at Beijing Tiantan Hospital were continuously included in the study. The demographic data of the patients were collected, and the fasting blood within 24 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…[25][26][27][28] Furthermore, among patients with an acute ischemic stroke, higher serum sICAM-1 levels influenced poor outcomes. 17 A similar relationship in patients with ICH had previously only been reported in case series and small cohort studies including up to 60 patients with ICH. These studies have suggested an association between sICAM-1 levels in peripheral blood or cerebrospinal fluid and poor functional outcome 29,30 ; however, the low statistical power precluded adjustment for covariates that influence outcome.…”
Section: Discussionsupporting
confidence: 74%
“…[25][26][27][28] Furthermore, among patients with an acute ischemic stroke, higher serum sICAM-1 levels influenced poor outcomes. 17 A similar relationship in patients with ICH had previously only been reported in case series and small cohort studies including up to 60 patients with ICH. These studies have suggested an association between sICAM-1 levels in peripheral blood or cerebrospinal fluid and poor functional outcome 29,30 ; however, the low statistical power precluded adjustment for covariates that influence outcome.…”
Section: Discussionsupporting
confidence: 74%
“…sICAM-1 concentrations have been associated with an increased risk of total stroke in healthy women [ 37 ] and an increased risk of future coronary or ischemic stroke events in chronic coronary heart disease [ 38 , 39 ]. In addition, sICAM-1 has also been associated with unfavorable outcome, evaluated as mRS, in ischemic patients [ 40 , 41 ]. However, to our knowledge, the results of the present study show for the first time that the concentration of sICAM-1 is associated with stroke recurrence in patients with carotid stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such molecular changes could be detected by serum biomarkers. For example, interleukin 6 (IL-6) [ 23 26 ] and intercellular adhesion molecule (ICAM-1) could represent the inflammation level [ 23 , 27 , 28 ], 8-hydroxy-2′-deoxyguanosine (8-OHdG) [ 29 , 30 ] and heme oxygenase-1 (HO-1) could provide the information of oxidative stress [ 31 35 ], and brain-derived neurotrophic factor (BDNF) could be an indicator of neuroplasticity [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%